Body brain life: A randomized controlled trial of an online dementia risk reduction intervention in middle‐aged adults at risk of Alzheimer's disease. Issue 1 (10th June 2015) - Anstey, Kaarin J.; Bahar‐Fuchs, Alex; Herath, Pushpani; Kim, Sarang; Burns, Richard; Rebok, George W.; Cherbuin, Nicolas
Abstract: Objective: To examine the efficacy of body brain life (BBL), a 12‐week online dementia risk reduction intervention. Methods: BBL was evaluated in a randomized controlled trial in 176 middle‐aged adults with >2 risk factors and <2 protective factors for Alzheimer's disease (AD) assessed on a brief screening instrument. Participants were randomized to BBL, BBL plus face‐to‐face group sessions (BBL + FF) or active control (control). Score on the Australian National University‐Alzheimer's disease risk index (ANU‐ADRI), a validated index of AD risk, was the primary outcome measure assessed at baseline, 12, and 26 weeks. Results: A group by time interaction at 26 weeks showed a significant reduction in ANU‐ADRI score for BBL compared with control. Planned contrasts showed the BBL and BBL + FF groups had improvement in ANU‐ADRI scores at 12 weeks (BBL + FF: z = −0.25; P = .021; BBL: z = −0.25; P = .008) and 26 weeks (BBL + FF: z = −0.48; P < .001; BBL: z = −0.28; P = .004) due to increase in protective factors. Conclusions: This short intervention resulted in dementia risk reduction. Online dementia risk reduction interventions show promise for reducing the overall dementia risk in middle‐aged adults with multiple risk factors. Clinical Trial Registration: The study is registered under Trial Registration: Reg. # ACTRN12612000147886.